Investigating the impact of inflation on building materials prices in construction industry - Musarat, M.A. (Elsevier Ltd, 2020)
In spite of the advancement in the management of the construction industry, construction projects still facing the issue of cost overrun. Many factors influence the cost overrun but one of the most critical is the inflation rate, which plays a vital role in deviating prices of construction materials during the project lifecycle. Therefore, this study aims to investigate the behaviour of building materials prices and their correlation with the inflation rate. The Spearman test was adopted to measure the correlation between the building materials prices and the inflation rate. It was revealed that a significant positive and negative relationships between the inflation rate and the building materials prices exist, indicating that the change in the inflation rate will also affect the prices which will result in deviating the initial budget of a project. The correlation was investigated by the individual materials of cement, steel reinforcement, plumbing works, sanitary fitting, ironmongery, bricks, roofing, ceiling board, paints and plywood. Every materials group is representing an individual industry thus it can be concluded that the inflation rate is influencing these industries as well. Therefore, it is essential to consider the inflation rate while calculating the budget at the beginning of the construction projects, with a recommendation to develop a budget estimation model which can incorporate the changing behaviour of the building materials prices due to the inflation rate along with other essential parameters in setting up the project budget. Â© 2020 Elsevier Ltd